Validity of the ESC Risk Assessment in Idiopathic Pulmonary Arterial Hypertension in China - Gong, Su-Gang; Wu, Wen-Hui; Li, Chao; Zhao, Qin-Hua; Jiang, Rong; Luo, Ci-Jun; Qiu, Hong-Ling; Liu, Jin-Ming; Wang, Lan; Zhang, Rui (Frontiers in Cardiovascular Medicine, 2021)
Background: The 2015 European pulmonary hypertension (PH) guidelines recommend a risk stratification strategy for pulmonary arterial hypertension (PAH). We aimed to investigate the validation and potential prognostic information in Chinese patients. Methods: The risk assessment variables proposed by the PH guidelines were performed by using the WHO function class, 6-min walking distance, brain natriuretic peptide or its N-terminal fragment, right arterial pressure, cardiac index, mixed venous saturation, right atrium area, pericardial effusion, peak oxygen consumption, and ventilatory equivalents for carbon dioxide. An abbreviated version also was applied. Results: A total of 392 patients with idiopathic PAH (IPAH) were enrolled between 2009 and 2018. After a median interval of 13 months, re-evaluation assessments were available for 386 subjects. The PAH guidelines risk tool may effectively discriminate three risk groups and mortality (p < 0.001) both at the baseline and re-evaluation. Meanwhile, its simplified risk version was valid for baseline and accurately predicted the risk of death in all the risk groups (p < 0.001). At the time of re-evaluation, the percentage of low-risk group has an increase, but a greater proportion achieved the high-risk group and a lesser proportion maintained in the intermediate-risk group. Conclusion: The 2015 European PH guidelines and its simplified version risk stratification assessment present an effective discrimination of different risk groups and accurate mortality estimates in Chinese patients with IPAH. Changes of risk proportion at re-evaluation implicated that natural treatment decisions may not be consistently with goal-oriented treatment strategy.